ANALISIS DUKUNGAN KELUARGA TERHADAP EFIKASI DIRI PADA PASIEN STROKE: LITERATURE REVIEW - Mashita Dewi; Safri Safri; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Stroke is a permanent neurological disease caused by disruption of blood flow to the brain, usually lasts 24 hours or more. Stroke can cause disability, both minor and severe. The impact of disability varies, from a decrease in the quality of life of an individual after a stroke due to disrupted activities, needing help from family / other people, to being completely dependent on other people, therefore, family support is needed in the care of stroke patients. This study aims to determine the relationship between family support and self-efficacy in stroke patients. This study uses a literature review method. Search for published articles using google scholar and the Garuda portal, keywords in English, namely family support AND self-efficacy AND stroke patient, and in Indonesian includes family support + self-efficacy and stroke patients in the 2016-2020 range. Of the 516 articles that were screened, 7 research articles were reviewed. The literature review shows that from 7 articles the majority of respondents' ages are ≥ 46 years (41.15%) and the majority are male (51.38%). The results of the description of family support from 4 articles, most of the respondents had quite good family support (54.6%). While the results of the self-efficacy description from 3 articles, most of the respondents experienced high self-efficacy (45.22%). Recommendations for health workers to explain the importance of providing family support to family members, especially stroke patients. Keywords: Family support, self efficacy, stroke